Audiovisual Communication and Subtitling from the Perspective of Semiotic Cohesion: A Case Study of “Garden of Eden” - Ulvydienė Huber, Loreta; Lideikytė, Viktorija (Respectus Philologicus, 2021)
Films as multimodal products have an increasing entertainment value, so the need to transfer them to other cultures arises. Audiovisual translation (AVT) becomes the only practice to translate and adapt multimodal discourse to various audiences. Together with audio description, that translates the visual into spoken language completing in this way the sounds and dialogues of films, subtitling deals with the changes within the semiotic system. Since subtitles have to interact and work in synchrony with dialogue and image, a great variety of problems arises when this translation mode is employed because a lot of constraints that exist. However, semiotic cohesion between subtitles and other elements such as moving pictures, verbal and non-verbal language and camera editing should be retained. The aim of the paper is to analyse the cases of semiotic cohesion in the English subtitles of the Lithuanian film Garden of Eden (2015). The research is carried out within the framework of multimodal discourse analysis that permits the incorporation of all identifiable communicative modes. The course of practical investigation crystallises out into three underlying directions: assessment of semiotic cohesion, identification of particular form(s) of semiotic cohesion depending on its (dis)appearance on screen and the analysis of the selected instances.